Developing a user-oriented approach to selection of geospatial data based on fuzzy logic - Bielcheva, Ganna; Manakova, Nataliia; Makogon, Nataliia (Eastern-European Journal of Enterprise Technologies, 2016)
The work considers the approach to selection of geospatial data, oriented towards the user's requirements. The methods and models are presented for evaluation of quality and selection of the sets of spatial data with the aid of fuzzy logic. The model of evaluation of the quality of spatial data was designed, which fully agrees with the elements of quality of a series of the international standards ISO 19157. The model makes it possible to comprehensively consider the requirements of user in the selection of spatial data for the formation of information provision of GIS–applications. Within the framework of the model, the methods of selection of spatial data according to the indicators of thematic and positioning accuracy were developed. The method of thematic accuracy is realized under conditions of the lack of the reference cartographic material. The method of selection of spatial data according to the indicator of positioning accuracy provides for the possibility of correcting an error of the planned and high-altitude accuracy and presents the result in the form of expert recommendations. Furthermore, this approach is realized in the prototype of a system, which makes it possible for the users to consider their requirements in conjunction with the indicators of quality of geospatial data. This system allows forming information provision of GIS-applications, and its verification in several projects of different thematics demonstrated positive results of taking onto account the needs of users at the stage of selecting the data.